Proust’s Ruskin: From Illustration to Illumination - Emily Eells (Cahiers Victoriens et Edouardiens)
This article focuses on Proust’s response to the visual component of Ruskin’s works, highlighting how the Ruskinian dialectic of word and image gave impetus to Proust’s Recherche du temps perdu. It borrows terms from Ruskin’s works to define their aesthetic relationship: that of ‘incrustation’, meaning both the way Venetian architects covered brick walls with marble and the way they decorated walls with precious stones, is applied here to define Ruskinian intertextuality in Proust’s text, as it involves both textual layering and the use of quotation as ornamentation. Ruskin’s concept of ‘reciprocal interference’ is adopted to designate intermediality and to suggest that Proust not only borrowed from Ruskin’s text but enriched it through his translation and annotation of it. Although his translations did not reproduce the original illustrations, his two-part article on Ruskin in the Gazette des Beaux Arts (April and August 1900) included reproductions of Giotto’s ‘Charity’ and Ruskin’s drawing of the sculpted figure from the façade of Rouen cathedral. These two figures are likened to ‘noble grotesques’ here, as they correspond to Ruskin’s definition of an allegorical figure conveying an inexpressible truth through symbolism. My argument here is that Proust appropriated those two illustrations and transformed them into illuminations, in the sense that Ruskin gave to that term in Modern Painters.